2014
DOI: 10.1163/22134808-00002460
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Future for Sensory Substitution Outside Academic Laboratories?

Abstract: Sensory substitution devices (SSDs) have been developed with the ultimate purpose of supporting sensory deprived individuals in their daily activities. However, more than forty years after their first appearance in the scientific literature, SSDs still remain more common in research laboratories than in the daily life of people with sensory deprivation. Here, we seek to identify the reasons behind the limited diffusion of SSDs among the blind community by discussing the ergonomic, neurocognitive and psychosoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 79 publications
0
73
1
Order By: Relevance
“…Provision of support and training was identified as a factor in the abandonment of traditional assistive technology (Phillips & Zhao, 1993;Batavia & Hammer, 1990) and it has been suggested as a factor in improving SSAD use (Elli et al, 2014;Maidenbaum et al, 2014). In the present paper, following a summary of the applications of SSADs and the reasons why they may be rejected, we suggest how the findings of cognitive science can be leveraged to improve the process of learning to use an SSAD.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Provision of support and training was identified as a factor in the abandonment of traditional assistive technology (Phillips & Zhao, 1993;Batavia & Hammer, 1990) and it has been suggested as a factor in improving SSAD use (Elli et al, 2014;Maidenbaum et al, 2014). In the present paper, following a summary of the applications of SSADs and the reasons why they may be rejected, we suggest how the findings of cognitive science can be leveraged to improve the process of learning to use an SSAD.…”
Section: Introductionmentioning
confidence: 78%
“…Other research has found that users value device performance, particularly how the device meets expectations of performance, reliability, durability, comfort, safety and ease of use (Batavia & Hammer, 1990;Riemer-Reiss & Wacker, 2000). Several of the factors highlighted from research into traditional assistive technology been repeated by reviews focusing on SSADs, along with some that are specific to SSADs: lack of availability, lack of awareness of their existence, concerns about their appearance, cost, difficulty in setting up, and the potential to mask important auditory cues in life (Maidenbaum et al, 2014;Elli et al, 2014). Some of these priorities have been addressed by SSAD researchers: to ensure that the device does not fall short of expected performance due to high expectations, Nau and colleagues begin their training program with an explanation of the capabilities and limits of the device (Nau et al, 2015b), and to improve ease of use, some groups have examined how intuitive the encoding of information is intuitive and easy to understand (Hamilton-Fletcher et al, 2016).…”
Section: Use and Non-use Of Assistive Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…Even today, the widespread adoption of SSDs (sensory substitution devices) outside of academia seems to face steep challenges. As suggested by Elli et al, this may be due to the fact that effectively coordinating issues arising from the different perspectives of ergonomics, neuroscience, and social psychology is a tricky business [5].…”
Section: Introductionmentioning
confidence: 99%